Letter to Senator Tom McClintock and a Letter to State Assembly member Hannah-Beth Jackson - Jane Tolmach:::::: (2001)
Two letters to Senator Tom McClintock and State Assembly Member Hannah-Beth Jackson urging them to pressure Gale Norton to reject a proposed casino in Oxnard, California.